Sleep quality mediates the effect of chronotype on resilience in the time of COVID-19. (3rd June 2021) - Bazzani, A.; Bruno, S.; Frumento, P.; Cruz-Sanabria, F.; Turchetti, G.; Faraguna, U.
ABSTRACT: This study aimed to explore the relationship between chronotype and resilience, sleep quality, and post-traumatic stress reactions during the first COVID-19 lockdown in Italy. An online survey was distributed through social networks during forced home confinement, collecting data from1298 participants of 19 different Italian regions. Chronotype was evaluated using the reduced version of the Morningness/Eveningness Questionnaire (rMEQ); sleep quality was assessed by the Pittsburgh Sleep Quality Index (PSQI); resilience levels were measured by the 10-item version of the Connor-Davidson Resilience Scale (CD-RISC10); post-traumatic stress reactions were assessed by the 6-item version of the Impact of Event Scale (IES6). Resilience and sleep quality were significantly lower in the evening compared to non-evening types, as well as in females as compared to males. Moreover, resilience was negatively correlated with post-traumatic stress reactions and positively correlated with sleep quality. A negative correlation was also reported between sleep quality and post-traumatic stress reactions. Sleep quality was identified as a possible mediator between chronotype and resilience, and between resilience and post-traumatic stress reactions, after controlling for age and sex. These findings provide new insights into the role of chronotype in adapting to continuous stressful situations. Sleep quality seems to mediate the causal path between the antecedents of resilience and the development of trauma. Further research is needed to explore the suitability of primary interventions based on chronobiology and sleep hygiene to mitigate the impact of pandemic-related home confinement measures on mental health among the general population.